Does governance affect compliance with IFRS 7? - Amal Yamani; Khaled Hussainey; Khaldoon Albitar (Journal of Risk and Financial Management, 2021)
Although there has been considerable research on the impact of corporate governance on corporate voluntary disclosure, empirical evidence on how governance affects compliance with mandatory disclosure requirements is limited. We contribute to governance and disclosure literature by examining the impact of corporate governance on compliance with IFRS 7 for the banking sector in Gulf Cooperation Council (GCC). We use a self-constructed disclosure index to measure compliance with IFRS 7. We use regression analyses to examine the impact of board characteristics, audit committee characteristics and ownership structure on compliance with IFRS 7. Using a sample of 335 bank-year observations for GCC listed banks over the period 2011-2017, we report evidence that corporate governance variables affect compliance with IFRS 7. However, the significance of these variables depends on the type of the regression model used. Our findings suggest that governance matters for mandatory disclosure requirements. So to improve the level of compliance, regulators, official authorities, and policymakers should intensify their efforts toward improving corporate governance codes, following up their implementation and enhancing the enforcement mechanisms.
Keywords: 330; corporate governance; GCC; IFRS 7 compliance